Research on the Sealing Performance of Segmented Annular Seals Based on Fluid–Solid–Thermal Coupling Model - Zhenpeng He; Lanhao Jia; Jiaxin Si; Ning Li; Hongyu Wang; Baichun Li; Yuhang Guo; Shijun Zhao; Wendong Luo (Lubricants)
High-speed segmented annular seals are often subjected to friction and wear, and the groove design on the sealing surface can effectively suppress this loss. For the purpose of improving the sealing performance, the segmented annular seal models of three structures are established, and the accuracy of the calculation model is verified by comparing with the previous results. Through fluid–solid–thermal coupled analysis, the flow field characteristics, opening characteristics, and leakage characteristics of the segmented annular seal under high working condition parameters were studied. The results show that the setting of the shallow groove forms the hydrodynamic effect by squeezing and hindering the flow of fluid in the clearance. The increase in rotational speed and pressure difference can promote the increase in the opening force, while the temperature has no significant effect on the opening of the seal. Seals with ladder-like grooves have the best opening performance, and seals without shallow grooves are already difficult to open under conditions of high pressure difference and large spring forces. Temperature and pressure difference are the main factors affecting the leakage of the seal, while the influence of the rotation speed is small. When the sealed pressure increases from 0.15 MPa to 0.4 MPa, the maximum increase in the leakage of the seal with specific groove design is 4.657 times the original. As the temperature rises from 420 K to 620 K, the maximum decrease in the three structures is up to 22.9%. Among the seals of the three structures, seals with ladder-like grooves have medium leakage. This research will contribute to the improvement of research methods for the sealing performance of segmented annular rings, especially for the evaluation of groove design and opening characteristics.